Relationship between Postmenopausal Estrogen Deficiency and Aneurysmal Subarachnoid Hemorrhage - Sadaharu Tabuchi (Behavioural Neurology)
Aneurysmal subarachnoid hemorrhage (SAH) is one of the most severe forms of stroke, which results from the rupture of a cerebral aneurysm. SAH is the only type of stroke with a female predominance, suggesting that reproductive factors may play a significant role in the etiology. Estrogen has important effects on vascular physiology and pathophysiology of cerebral aneurysm and SAH and, thus, potential therapeutic implications. There have been growing bodies of epidemiological and experimental studies which support the hypothesis of a significant relationship between estrogen deficiency and cerebral aneurysm formation with subsequent SAH. This hypothesis is the focus of this review as well as possible pathology-based therapeutics with regard to aspects of molecular pathophysiology, especially related to women’s health.